1977
DOI: 10.1007/bf02377838
|View full text |Cite
|
Sign up to set email alerts
|

Parasites, predators and other arthropods associated withMusca domestica and other flies breeding in bovine manure

Abstract: The species of flies breeding in bovine manure, their parasites and predators as well as other associated arthropods in 3 localities in and near Bangalore are recorded. The flies are Muaca domestiea L., Musca pattoni AUSTEN, Stomoxys calcitrans L., Physiphora aenea F., Physiphora demandata F., Sargus metallinus F., Sepsis thoracica R.-D., Sepsis nitens WIEDEMANN, Sphaerocera seabricula HAL. and Leptocera (Coproica) hirtula RONDANI. Four species of hymenopterous pupal parasites of these flies have been obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
3

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
1
1
3
Order By: Relevance
“…As an omnivorous species, M. domestica can use different substrates in the larval stage (Hewitt 1914). Although pig dung has been cited by various authors as one of the best substrates for development of this fly (Geetha Bai & Sankaran 1977, Senna-Nunes et al 1991, we found a lower density in this breeding ground, probably because the pigpens were cleaned and the dung removed regularly.…”
Section: Discussioncontrasting
confidence: 48%
“…As an omnivorous species, M. domestica can use different substrates in the larval stage (Hewitt 1914). Although pig dung has been cited by various authors as one of the best substrates for development of this fly (Geetha Bai & Sankaran 1977, Senna-Nunes et al 1991, we found a lower density in this breeding ground, probably because the pigpens were cleaned and the dung removed regularly.…”
Section: Discussioncontrasting
confidence: 48%
“…Segundo BALDUF (1935), histerídeos são comumente encontrados em plantas em decomposição, excremento e carne putrefata. Wenzel (1961), apud PECK (1968) afirmou que todas as larvas de histerídeos são predadoras e GEETHA BAI; SANKARAN (1977) consideraram os histerídeos como eficientes predadores de muscóides, sendo bastante promissores no controle biológico de moscas, isto talvez explique a baixa captura desta família, devido aos métodos utilizados.…”
Section: Resultsunclassified
“…Na ordem Coleoptera, destaca-se a família Staphylinidae com várias espécies de parasitóides de outros insetos. A subfamília Aleocharinae (Staphylinidae) possui algumas espécies de parasitóides associados ao esterco de gado bovino (Bai & Sankaran 1977, Merritt & Anderson 1977, Blume 1984) que atacam pupas de Diptera (Wharton 1979, Figg et al 1983. A ordem Hymenoptera compreende insetos de grande importância econômica, visto que alguns destes parasitóides são inimigos naturais dos chamados insetos-pragas e, muitas vezes, impedem a sua proliferação.…”
Section: Palavras-chave: Insecta Dipteraunclassified